IPTEKS PENGENDALIAN INTERN DALAM PEMBIAYAAN IMPLAN PADA PT. BANK SYARIAH MANDIRI KC. MANADO - Arifin M.H, Radila; Kalangi, Lintje (Universitas Sam Ratulangi, 2018)
BSM or PT. Bank Syariah Mandri is aone of the syariah banks, which in practice banking uses the principles of Islamic syariah. In syariah banking, currenty there are many products, one of which is payment without installments, which in Bank Syariah Mandiri has also been implemented through the BSM implant program. The more developed implant financing is, the more effective internal control is needed for the company. To find out how internal control in implant financing at PT. Bank Syariah Manado branch office can be said to be effective or not. We can assess the effectiveness of internal control in implant financing if analyzing each element of the internal control system consisting of the control activities, control environment, risk assessment, monitoring and Information and communication. Whit good internal control within the company, implant financing can ran effectively. Keywords: Internal Control, Implant Financing, BSM Implant